First Evidence for Wollemi Pine-type Pollen (Dilwynites: Araucariaceae) in South America - Macphail, Mike (2013)
Fil: Macphail, Mike. Department of Archaeology and Natural History. College of Asia and the Pacific. Australian National University. Canberra; Australia